Celiac disease in children - Anjum Saeed; Asaad Mohamed Assiri; Huma Arshad Cheema (Wolters Kluwer Medknow Publications, 2019)
Celiac disease (CD) is a chronic enteropathy due to ingestion of gluten and related products leading to villous injury and its various manifestations. It has a strong genetic tendency with the presence of human leukocyte antigen (HLA-DQ 2, DQ 8) in more than 98% of these patients with CD. Western studies documented 0.5%-1% prevalence of CD but it is not an uncommon condition in the Arabic peninsula. Classical gastrointestinal (GI) manifestations are common in the toddler's age group while non-GI manifestations predominate in the adolescents and older children. High-risk groups and associated conditions need special considerations for screening CD. European and Americans guidelines are available for diagnosing these children and recommend to screen with anti-tissue transglutaminase antibodies which have got very high sensitivity and specificity. North American guidelines recommend to do small bowel biopsies and interpreted by Marsh grading. Gluten-free diet for the rest of life is still a recognized therapy for these children under the supervision of an expert dietician dealing with CD. National awareness programs and seminars may help in identifying this underdiagnosed condition to avoid morbidity and mortality related to this lifelong disorder.